Multidisciplinary supportive care for improving survival and quality of life in motor neuron disease - Georgiou, Anastasios M. (My University, 2018)
Motor neuron disease (MND) is a progressive and fatal neurological condition. Riluzole is the only pharmacological agent that is currently prescribed for all MND types. It is currently suggested that a 100 mg daily dose is safe and probably prolongs median MND survival by about 2-3 months. There is evidence that multidisciplinary teams (MDTs) contribute to symptoms relief, QoL improvement and increases in survival rates in patients suffering from MND. As respiratory, nutritional and swallowing problems are amongst the most important factors that are associated with decreased QoL and shorter survival, a large and growing body of literature has been investigating the best evidence for respiratory and nutritional support in MND care.
Keywords: Evidence based practice; MND care; Motor neuron disease; Multidisciplinary care